2020
DOI: 10.21203/rs.3.rs-17806/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Withanone from Withania somnifera May Inhibit Novel Coronavirus (COVID-19) Entry by Disrupting Interactions between Viral S-Protein Receptor Binding Domain and Host ACE2 Receptor

Abstract: Background Newly emerged COVID-19 has been shown to engage the host cell ACE2 through its spike protein receptor binding domain (RBD). Here we show that natural phytochemical from a medicinal herb, Withania somnifera, have distinct effects on viral RBD and host ACE2 receptor complex. Methods We employed molecular docking to screen thousands of phytochemicals against the ACE2-RBD complex, performed molecular dynamics (MD) simulation, and estimated the electrostatic component of binding free energy, along with t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 44 publications
(53 reference statements)
0
63
0
Order By: Relevance
“…withanone from Withania somnifera, displayed signi cant docking with the binding interface of ACE2-RBD complex. 49 Sofosbuvir which showed least toxicity in the present study is a prodrug nucleotide analogue and has recently been proposed as an antiviral for the SARS-CoV-2 based on the similarity between the replication mechanisms of the hepatitis C virus and the coronaviruses. .…”
Section: Discussionmentioning
confidence: 79%
“…withanone from Withania somnifera, displayed signi cant docking with the binding interface of ACE2-RBD complex. 49 Sofosbuvir which showed least toxicity in the present study is a prodrug nucleotide analogue and has recently been proposed as an antiviral for the SARS-CoV-2 based on the similarity between the replication mechanisms of the hepatitis C virus and the coronaviruses. .…”
Section: Discussionmentioning
confidence: 79%
“…Recent work has demonstrated that COVID-19 infections have a large immune component and can result in the development of cytokine storm, a potentially life-threatening immune reaction in which the body release too many cytokines into the blood at a rapid rate [28]. Interestingly, at least three independent research groups have suggested that phytochemicals found in the plant Withania somnifera could be developed as a therapeutic agent against COVID-19 infection using molecular docking approaches [29][30][31]. Two of the groups reported that various Withanolides, such as WFA, should be able to bind to the viral S-protein receptor binding domain, thereby blocking or reducing interactions with host ACE2 receptor [29,30].…”
Section: Withaferin a As A Prospective Treatmentmentioning
confidence: 99%
“…Interestingly, at least three independent research groups have suggested that phytochemicals found in the plant Withania somnifera could be developed as a therapeutic agent against COVID-19 infection using molecular docking approaches [29][30][31]. Two of the groups reported that various Withanolides, such as WFA, should be able to bind to the viral S-protein receptor binding domain, thereby blocking or reducing interactions with host ACE2 receptor [29,30]. The third group reported that WFA and a separate withanolide, Withanone, are predicted to interact with the main protease of SARS-CoV-2, although WFA is predicted to have less of a binding a nity than an established N3 protease inhibitor used for baseline docking scores [31].…”
Section: Withaferin a As A Prospective Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ayurveda, "Rasayana botanicals" are used for rejuvenation by boosting the immune system and alleviating disease condition 19,20,21 . Of several known botanicals Asparagus racemosus (AR), Tinosporacordifolia (TC), and Withaniasomnifera (WS) are known to modulate the immune system and possess antiviral activities 19,20,22,23,8 .…”
Section: Introductionmentioning
confidence: 99%